Peru : Extending the Use of Natural Gas to Inland Provinces - World Bank (World Bank, Washington, DC, 2014)
The project's goal is to configure realistically the potential business units that are likely to be awarded in concessions to private operators. These conditions are comprised of: (i) the socioeconomic reality of regions and current and potential energy use; (ii) the current legislation governing natural gas, (iii) the framework of institutions at the national, regional, and district levels; (iv) the base infrastructure already in place and in operation in Camisea (upstream-midstream) upon which the project's trunklines will be extended; (v) the characteristics of the areas crossed by the potential route of Camisea Trunk Transport pipeline (CTT) with respect to the extended pipelines and the relevant environmental restrictions; (vi) the project's supply costs compared to the economic benefits contributed; (vii) the financial requirements of the business units, and the engineering and design of a combination of reasonable revenues and rates which will attract responsible users and investors to the regional supply systems.